Avalanche Analysis of Extended Feistel Network - Ibrahim, Subariah; Maarof, Mohd. Aizaini; Idris, Norbik Bashah (2005)
In general, block ciphers consist of one top-level structural model into which the round function F is plugged into. In order to analyze the security of a cipher, it is also important to study the intrinsic security provided by these top-level structural models. Most research focuses in determining F functions that yield secure Feistel Networks (FN). This paper analyses the structural models of a generalized concept of FN known as Extended Feistel Network (EFN). EFN splits the input blocks into n > 2 sub-blocks. Like conventional FN, EFN consists of a series of rounds whereby at least one sub-block is subjected to an F-function. The work examines the models in terms of its avalanche criterion in order to determine the optimal scheme suitable for the design of a flexible block size cipher. The analysis shows that EFN Type-II is the most optimal structural model for this design.